Estudos de estabilidade no sistema Ʋ andromedae A - Camargo, Bárbara Celi Braga [UNESP] (2015)
The system Ʋ Andromedae was the first multiple system discovered whose the central body belong to the main sequence. Despite to be a widely studied system your data still have uncertainties. The detection of planets orbiting the star Ʋ Andromedae A was made using the radial velocity method. This method only give us possible values of masses, which are dependent on the value of the target plane tilt. The mass of the planet Ʋ And c, for example, can have a mass range between 1:9MJ and 14:57MJ , depending on the chosen inclination. The planets have high eccentricity values, which is not explained by the Solar System formation method. At this moment we know four planets for this system. The fourth planet was predicted theoretically in 2011, with this, the works made until now, just included three other planets. First we conducted a brief literature review on the research done about the system Ʋ Andromedae, since the discovery of the first planet in 1997 until the fourth planet in 2011. We separate two models for our studies. We approach then the study of secular perturbation in the system Ʋ Andromedae A, we note that the model with large masses have a greater variation of eccentricity. In sequence presents a study on the stability of the fourth planet in different scenarios, showing that the model of small masses have a greater range of stability when compared to the model of large masses